2020
DOI: 10.1186/s12935-020-01180-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel biomarkers affecting the metastasis of colorectal cancer through bioinformatics analysis and validation through qRT-PCR

Abstract: Background: Tumor progression and distant metastasis are the main causes of deaths in colorectal cancer (CRC) patients, and the molecular mechanisms in CRC metastasis have not been completely discovered. Methods: We identified differentially expressed genes (DEGs) and lncRNAs (DELs) of CRC from The Cancer Genome Atlas (TCGA) database. Then we conducted the weighted gene co-expression network analysis (WGCNA) to investigate co-expression modules related with CRC metastasis. Gene ontology (GO), Kyoto Encyclopedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“… 31 , 32 Lian et al reported that MOGAT2 could have applications as a novel biomarker affecting the metastasis of colorectal cancer treatment. 33 So far, little is known about the existence of molecular links between MOGAT2 and HCC. In our study, however, MOGAT2 was found to be highly decreased which might indicate its protective role as a prognostic marker in HCC.…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 Lian et al reported that MOGAT2 could have applications as a novel biomarker affecting the metastasis of colorectal cancer treatment. 33 So far, little is known about the existence of molecular links between MOGAT2 and HCC. In our study, however, MOGAT2 was found to be highly decreased which might indicate its protective role as a prognostic marker in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…CRC developed through a multistep process from normal epithelium to adenoma and adenocarcinoma, which can eventually metastasize to different organs [ 5 ]; it was shown that the transition of CRC cells from early stages to late stages (metastasis) is associated with a significant change in the cellular gene expression profile [ 6 ]. These genetic alterations have led to the emergence of the novel strategies for personalized medicine programs [ 7 , 8 ]. Moreover, the correlation between colorectal inflammation and increased colitis-associated tumorigenesis has been identified in some epidemiological and clinical studies [ 9 , 10 ], which is characterized by high mortality and is closely associated with inflammatory bowel disease [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many CRC models have reported that CHP2, GNAI1, and RETNLB are important to core pathway genes in the progression of CRC. Several genes were identified as biomarkers affecting CRC metastasis, including ChP2, and their low expression in CRC cell lines was confirmed, compared with normal colorectal epithelial cell lines (Liang et al, 2016;Lian et al, 2020;Ma et al, 2020). SPP1 levels were found to be increased in the blood of CRC patients, and their expression was related to a poor prognosis.…”
Section: Discussionmentioning
confidence: 89%